Transplantation of CCR5∆32 Homozygous Umbilical Cord Blood in a Child With Acute Lymphoblastic Leukemia and Perinatally Acquired HIV Infection. (22nd May 2018) - Rothenberger, Meghan; Wagner, John E; Haase, Ashley; Richman, Douglas; Grzywacz, Bartosz; Strain, Matthew; Lada, Steven; Estes, Jacob; Fletcher, Courtney V; Podany, Anthony T; Anderson, Jodi; Schmidt, Thomas; et al.
Abstract: Background: Allogeneic hematopoietic cell transplantation (allo-HCT) in a CCR5∆32 homozygous donor resulted in HIV cure. Understanding how allo-HCT impacts the HIV reservoir will inform cure strategies. Methods: A 12-year-old with perinatally acquired, CCR5-tropic HIV and acute lymphoblastic leukemia underwent myeloablative conditioning and umbilical cord blood (UCB) transplantation from a CCR5∆32 homozygous donor. Peripheral blood mononuclear cells (PBMCs) and the rectum were sampled pre- and post-transplant. The brain, lung, lymph node (LN), stomach, duodenum, ileum, and colon were sampled 73 days after transplantation (day +73), when the patient died from graft-vs-host disease. Droplet digital polymerase chain reaction (ddPCR) and in situ hybridization (ISH) were used detect the HIV reservoir in tissues. CCR5 and CD3 expression in the LN was assessed using immunohistochemistry (IHC). Results: HIV DNA (vDNA) was detected in PBMCs by ddPCR pretransplant but not post-transplant. vDNA was detected by ISH in the rectum at days –8 and +22, and in the LN, colon, lung, and brain day +73. vDNA was also detected in the lung by ddPCR. IHC revealed CCR5+CD3+ cells in the LN postmortem. Conclusions: HIV was detected in multiple tissues 73 days after CCR5∆32 homozygous UCB allo-HCT despite myeloablative conditioning and complete donor marrow engraftment. These results highlight the importance of analyzing tissue during HIV cure interventions and inform the choice of assay used to detect HIV in tissue reservoirs.